Forecasting explosions at Sinabung Volcano, Indonesia, based on SO2 emission rates - Kunrat, Syegi; Kern, Christoph; Alfianti, Hilma; Lerner, Allan H. (Frontiers in Earth Science, 2022)
Sinabung volcano (Sumatra, Indonesia) has been in a state of eruption since August 2010 with frequent explosions producing eruptive columns that rise many kilometers into the atmosphere and at times sending pyroclastic density currents down the southeast flanks. A network of scanning DOAS instruments was installed on the volcano’s east flank in 2016 to measure the emission rate of SO2 on days with conducive wind directions. Analysis of the DOAS data from October 2016 to September 2017 revealed that passive SO2 emissions were generally slightly lower in the 5 days leading up to explosive events (100 t/d) than is common in 5-day periods leading up to explosive quiescence (200 t/d). The variability of passive SO2 emissions also had a slightly wider range of values before days with explosions than before days without explosions. These observations can be explained by a seal-failure model, where the sealing of the volcanic conduit blocks gas emissions and leads to pressurization and potential explosions. We develop a forecasting methodology that allows calculation of a relative daily explosion probability based solely on measurements of the SO2 emission rate in the preceding days. We then calculate forecast explosion probabilities for the remaining SO2 emissions dataset (October 2017 – September 2021). While the absolute accuracy of forecast explosion probabilities is variable, the method can inform the probability of an explosion occurring relative to that on other days in each test period. This information can be used operationally by volcano observatories to assess relative risk. The SO2 emissions-based forecasting method is likely applicable to other open vent volcanoes experiencing dome-forming eruptions.